Getting saved in America : Taiwanese immigration and religious experience - Chen, Carolyn, 1971- (Princeton University Press, 2008)
What does becoming American have to do with becoming religious? Many immigrants become more religious after coming to the United States. Taiwanese are no different. Like many Asian immigrants to the United States, Taiwanese frequently convert to Christianity after immigrating. But Americanization is more than simply a process of Christianization. Most Taiwanese American Buddhists also say they converted only after arriving in the United States even though Buddhism is a part of Taiwan's dominant religion. By examining the experiences of Christian and Buddhist Taiwanese Americans, Getting Saved.